READING, RETELLING, REHEARSAL AND VIDEOTAPING (RRRV) TO IMPROVE SPEAKING ABILITY IN ENGLISH - andy andy; Muhammad Suharto (JURNAL ILMIAH BAHASA DAN SASTRA, 2017)
RRRV (Reading, Retelling, Rehearsal, and Videotaping) learning method is a verbal English learning method which is useful to combine reading ability and retelling a story preceeded by doing rehearsal and therefore students’ verbal competence can be increased during this process. This research aims to test the effectiveness in applying RRRV to merely RRR without V. The subjects are students at faculty of language and literature consisting of group A (RRRV) and group B (RRR) only. Pre-test of English proficiency is given to group A and group B before treatment is presented to both of them. The result of the test is used to ascertain whether the goups are homogenous in terms of their English proficiency. It shows that both group A and B have equal ability in TOEFL test result, thus both groups are considered to be homogenous and hence different treatment are given to group A and B. After treatments, data is taken from both groups based on post-test result by retelling the content of story and including video-taping for group A and audio-taping for group B. Meanwhile, data is taken from questionnaire consists of students’ opinion in applying RRRV and RRR method. Data from the test is stored in SPSS version 22 and inferential statistics of independent sample t-test analysis is used to examine if there is significant difference between the use of RRRV and RRR only. The result of questionnaire is analysed using descriptive statistics. Hopefully, the resulf of this research is able to contribute to the body of knowledge about how to improve verbal English proficiency.